Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Chiquitta Kristiolina Ompusunggu, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The value of the company is an investor perception of companies associated with stock price. This research was conducted to investigate the influence of Investment Decisions, Funding Decision, Dividend Policy and Profitability toward firm value in companies listed in Indonesia Stock in 2016 – 2018 period. The population in this study as many as 111 companies, and by using purposive sampling techniques, the obtained 37 manufacturing companies in the sample. Data processing techniques using data panel analysis using Eviews 9.0. The result of this study is Investment Decision, Funding Decision and Dividend Policy do not have significant affect to firm value while Profitability have significant to firm value.